A Research Paper on New Generation Gym Mat (International Journal of Innovative Research in Computer Science & Technology, 2021)
Gym has been more popular in recent  years since it aids in the maintenance of one's health,  increases flexibility, improves concentration, and  motivates individuals to live a healthy and tranquil life.  People used to practice Gym on any surface, but today  they prefer to do it on a Gym mat since it offers greater  comfort and ease. The primary purpose of a Gym mat is  to prevent or minimize hand and foot slippage. The Gym mats that have been created so far are not automated and  cannot be controlled using a speech system. The  researcher suggested an automated mat that can be  controlled via a speech system in this article.  Temperature sensor, weight sensor, movement sensor,  piezoresistive sensor, pressure sensor, vibrator, display  screen, roller with direct current (DC) motor, voice  system, AI camera, and AI-based controller are all  included in this mat. This Gym mat is superior to the  previous one since it is automated and can recommend  workouts based on the user's age. The automated Gym mat has a promising future since it may be further  customized by incorporating new technologies and  mechanics.
Keywords: Artificial Intelligence (AI) camera; Controller; Sensors; Voice System; Gym mat